2017
DOI: 10.1371/journal.pone.0184385
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 protein expression and subcellular localization in primary breast cancer: Automated digital microscopy analysis of tissue microarrays

Abstract: PurposeMutations in BRCA1 are associated with familial as well as sporadic aggressive subtypes of breast cancer, but less is known about whether BRCA1 expression or subcellular localization contributes to progression in population-based settings.MethodsWe examined BRCA1 expression and subcellular localization in invasive breast cancer tissues from an ethnically diverse sample of 286 patients and 36 normal breast tissue controls. Two different methods were used to label breast cancer tissues for BRCA1: (1) Dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
3
13
1
1
Order By: Relevance
“…In this study we found that BRCA1 protein was expressed in 10% of breast cancer, this study is supported by study of Dokyung et al [13]. who reported that BRCA protein was expressed in 24.7% of breast cancers, In the present study we also found the expression of BRCA1protein in breast cancer is higher than in normal breast lesion, this finding is inconsistent with the study of [14] who reported that a high uniform expression of BRCA1 was observed in normal breast tissue while absent or reduced expression was found only in malignant tissues.…”
Section: Discussioncontrasting
confidence: 78%
“…In this study we found that BRCA1 protein was expressed in 10% of breast cancer, this study is supported by study of Dokyung et al [13]. who reported that BRCA protein was expressed in 24.7% of breast cancers, In the present study we also found the expression of BRCA1protein in breast cancer is higher than in normal breast lesion, this finding is inconsistent with the study of [14] who reported that a high uniform expression of BRCA1 was observed in normal breast tissue while absent or reduced expression was found only in malignant tissues.…”
Section: Discussioncontrasting
confidence: 78%
“…We detected BRCA1 in the nuclei and cytosol of vCTs. Cytosolic BRCA1 location has been associated with highly proliferating breast cancer tumors [46]. Its presence in the cytosol of vCTs reflects the high proliferative potential, as can be expected from the trophoblast stem cell population.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 20% of sporadic breast tumors [14] did not show BRCA1 staining in either the nucleus or cytoplasm, which demonstrated a defect in protein production. In some cases, breast tumor cells showed cytoplasmic BRCA1 retention along with a loss of nuclear staining [15], which implied a defect in nuclear transportation [42,43]. These BRCA1 protein-loss tumor cells were associated with poor prognosis and might induce high BRCA1 gene expression via auto-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of BRCA1 function increases ER-coactivator association in tamoxifen treated cancer cells, which leads to tamoxifen resistance [10]. In fact, decreased BRCA1 protein staining is commonly observed in sporadic breast cancers [14,15] and this phenomenon is associated with high histologic grades [16][17][18] and short disease-free survival [19]. It is certain that such association is related to an E-ER signaling pathway.…”
Section: Introductionmentioning
confidence: 99%